Cyber (In)Security in Metaverse: New Threats Old Measures? - AKYEŞİLMEN, Nezir (Cyberpolitik Journal, 2022)
As can be seen from Google searches, metaverse , which became one of the most popular concepts – even number one - in cyberspace in late 2021, has gained increasing popularity in literature. Metaverse, for some a more advanced stage of the Internet, is based on blockchain technology, virtual reality and a real-life like virtual space consisting of avatars, three-dimensional glasses, headsets and related instruments. This domain will increase the connection between users, diversify online business and transactions, extend the time spent on the Internet, and accelerate online cooperation and collaboration. While this virtual space increases digitalization, it will add new comfort areas to our lives and provide convenience. However, it is a fact that it will bring new risks and threats. Therefore, security in the metaverse will become an important issue of the future. Ensuring cybersecurity in metaverse will primarily require the development of new measures against new threats in metaverse, in addition to traditional cybersecurity measures. Although it is safer against technical attacks and malicious software for now due to blockchain infrastructure, it is quite week against social-based attacks such as social engineering, phishing, spam messages, fraud, as in today's cyber space. In this respect, the user is the weakest link in cybersecurity – as it is the case in today’s cyber space- comes to the fore here as well. In this context, it would not be wrong to say that an effective and rights-based digital citizenship education, which will improve the cybersecurity capacity of users, will be an important measure in addition to traditional measures to ensure cybersecurity in the metaverse.